Description of The Professional Identity of First-Level Clinical Medical Students and The Various Factors That Facilitate Its Formation - Haryanti, Nathalia; Puspadewi, Natalia; Juliawati, Veronica Dwi Jani; Anastasia, Gisella (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Identity formation is a longitudinal and continuous process. This study aimed to define: 1) the characteristics of professional identity (PI) of five first-year clinical students; 2) the role of clinical teachers and other factors that influenced PI formation during clinical rotations, and 3) how the learning process at the clinical level facilitates students to participate and gain recognition.Method: This was a qualitative phenomenological study. This study was open to any first-year clinical students who were undergoing their major clinical at the time of data collection and met the inclusion criteria. Indepth interview was conducted as soon as an interested student contacted the research team. At the end, five first-year clinical students were included in this study. All interviews were voice recorded and transcribed verbatim. Data was analyzed using thematic analysis.Results: a) Technical skills and internal values are two main components that formed their professional identities; b) Clinical teachers act as students’ role model and provide participants with the necessary recognition and opportunities to participate in a community of practice, which subsequently supported their PI formation during clinical rotation; c) participants’ PI formation was supported by various learning experiences embedded in their medical school’s curriculum. Conclusion: Technical skills and internal values are two professional identity components that defined a professional physician. Curriculum design as well as clinical teachers who closely interact with clinical students during their clinical rotations are two essential factors in creating a conducive learning environment that supports participants’ PI formation.